2021
DOI: 10.1002/pan3.10202
|View full text |Cite
|
Sign up to set email alerts
|

Soap operas will not wash for wildlife

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…commissioning bodies) and target viewership all shape producers' choices of narrative framing and what to include. While affective storytelling and arresting aesthetics remain central (Somerville et al, 2021) F I G U R E 1 An illustration of the process by which visual media impacts human-nature interactions. Visual media is produced in various forms with different purposes in mind (Section 2.1).…”
Section: Productionmentioning
confidence: 99%
“…commissioning bodies) and target viewership all shape producers' choices of narrative framing and what to include. While affective storytelling and arresting aesthetics remain central (Somerville et al, 2021) F I G U R E 1 An illustration of the process by which visual media impacts human-nature interactions. Visual media is produced in various forms with different purposes in mind (Section 2.1).…”
Section: Productionmentioning
confidence: 99%
“…While the anthropomorphic approach in film (particularly in the documentary genre) has been heavily criticised for a variety of reasons (e.g. see Bousé, 2011;Somerville et al, 2021), it can also be a valuable tool for making the non-human more relatable to an audience, thus making it easier to identify and/or empathise with them (Tam, 2015;Tam et al, 2013). Indeed, Tam et al (2013) found that anthropomorphism resulted in greater connectedness to nature and subsequent PEB.…”
Section: Identity the Self And Environmental Filmsmentioning
confidence: 99%
“…Somerville et al (2021) most recently outline examples of these falsified narratives in 2018's Dynasties, where frequently the framing of situations and the accompanying narratives, or 'storytelling', are at odds with the scientific evidence. One such example occurs in the episode following a pack of African wild dogs, where exaggerated tensions between lions and wild dogs are created through the narrative, pitting the species against each other with little acknowledgement of the realities of coexistence within their home ranges (Somerville et al, 2021). Accusations of misrepresentation have also been voiced in relation to the controversial inclusion of footage taken from captive and studio settings in productions such as Frozen Planet and Blue Planet II (BBC News, 2011;Carrington, 2017aCarrington, , 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, portrayals of apparently healthy ecosystems risk contributing to extinction denialist rhetoric (Lees et al, 2020). These concerns over misrepresentation voiced in the media are not reserved to journalists alone but rather amplify the sentiments reflected among academics both on the topic of wider environmental portrayals (Louson, 2018), but also more specific treatment of species portrayals such as anthropomorphism and false narratives (Bousé, 1998; Somerville et al, 2021). Somerville et al (2021) most recently outline examples of these falsified narratives in 2018's Dynasties , where frequently the framing of situations and the accompanying narratives, or ‘storytelling’, are at odds with the scientific evidence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation